(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2021)
The family Bathylagidae (deep-sea smelts) is a group of marine meso- and bathypelagic argentiniform fish with relatively poor fossil record. The described specimens from the Egerian deposits of the Krumvíř locality, named Krumvirichthys brzobohatyi gen. et sp. nov. represent oldest verifiable record of the bathylagid fishes known up to date. The new genus and species is characterized by semicircular orbitosphenoid at the dorsal section of the orbit, basisphenoid developed, opercle bearing posterodorsally developed large process, opercle and subopercle posteroventrally radially grooved, preopercle with triangle-shaped process at the posteroventral margin of the bone, cleithrum with enlarged triangle-shaped posterior lamina, no postcleithra, pectoral fin with eight or nine rays and elongated up to the level of the insertion of the dorsal fin, pelvic fin with nine rays inserted just below the middle of the dorsal fin, dorsal fin with ten or eleven rays, up to eight supraneurals presented in front of dorsal fin, vertebral column consists by at least 23 + 21 vertebrae, body covered by thin and large cycloid scales, and lateral line scales reinforced around tubular part. The combined presence of the orbitosphenoid and basisphenoid in new species particularly reminds the Recent bathylagid genera Lipolagus, Melanolagus, and Bathylagichthys.